(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The important condition of high culture of verbal speech is a mastering the system of language in all aspects or tiers – sound, including intonational, lexical, grammatical and stylistic. Investigating the question of sound and intonational expressiveness of verbal speech methodists establish an indissoluble connection between work on development of verbal speech and forming of expressive reading skills based on students’ vocal hearing. The purposeful work on the expressive reading and verbal speech brings students joy and pleasure. Deliberate work on important facilities of expressiveness as a pledge of intelligent speech and expressiveness of the mother tongue is obvious to the elementary school teacher.